(untitled) (Revista Brasileira de Plantas Medicinais, 2000)
The present study attempts to record the folk medicinal uses of 97 plants of the county of Tanquinho, State of Bahia. Northeastern Brazil. Data were obtained from September to November 1997 by conducting open-ended interviews with practitioners and users of local traditional medicine. The most representative botanic families were Euphorbiaceae, Solanaceae, Lamiaceae, Poaceae, Asteraceae, Anacardiaceae, Verbenaceae, and Cucurbitaceae. Plant-based remedies are used to cure numerous ailments, such as influenza, conjunctivitis, bronchitis, lithiasis, tuberculosis, asthma, fever, diarrhea, toothache, dysentery, cough, and cystitis. The value of medicinal resources derived from plants is very significant. Ethnobotanical knowledge is to be included into programs of medicinal plant conservation in order to provide medicines, food, and income to the people.